1995
DOI: 10.1007/bf02372679
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofMetarhizium anisopliae (DAT F-001) concentration and exposure time on the survival of the subterranean pasture pest,Adoryphorus couloni (Col.: Scarabaeidae)

Abstract: The virulence of the DAT F-001 isolate of Metarhizium anisopliae for Adoryphorus couloni was tested by exposing final instar larvae (L3) to concentrations of 101 to 107 spores/g in a sand-peat mix for up to ll2days at 20~176 All concentrations were pathogenic to L3 larvae and survival was dependent on concentration and correlated with exposure time. The time to .kill 50% of the treated larvae (LTso) ranged from 18.9 days (107spores/g) to 82.7 days (101 spores/g). The effect of DAT F-001 on feeding by L3 larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In agreement with this, Rath and Worledge (1995) demonstrated that M. anisopliae DAT F-001 at concentrations of 10 1 to 10 7 spores/g potting mix was pathogenic to the larvae of Adoryphorus couloni Burmeister (Coleoptera: Scarabaeidae).…”
Section: Discussionsupporting
confidence: 56%
“…In agreement with this, Rath and Worledge (1995) demonstrated that M. anisopliae DAT F-001 at concentrations of 10 1 to 10 7 spores/g potting mix was pathogenic to the larvae of Adoryphorus couloni Burmeister (Coleoptera: Scarabaeidae).…”
Section: Discussionsupporting
confidence: 56%
“…These anti-feedant properties are probably due to so-called destruxins (cyclic depsipeptides), secreted by the fungus (Amiri et al, 1999(Amiri et al, , 1997Pais et al, 1981). These reduced feeding rates were shown for M. anisopliae infecting the thrips Megalurothrips sjostedti (Ekesi and Maniania, 2000), on the crucifer pests Plutella xylostella and Phaedon cocleariae (Amiri et al, 1999(Amiri et al, , 1997, but other studies did not report it (Rath and Worledge, 1995). Other examples of this phenomenon include the fungi M. anisopliae Xavoviride on the grasshoppers/locusts Zonocerus variegatus (Thomas et al, 1997), Locustana pardalina (Mueller, 2000), and Schistocerca gregaria (Moore et al, 1992;Seyoum et al, 1994), Beauveria bassiana (Balsamo) Vuillemin on the armyworm Spodoptera exigua Hübner (Hung and Boucias, 1992), and the microsporidium Nosema locustae Canning on the grasshopper Melanoplus sanguinipes (Fabricius) (Johnson and Pavlikova, 1986).…”
Section: Introductionmentioning
confidence: 88%
“…Our targeted host insect is wireworm, a soil insect infesting belowground plant parts, such as sweetpotato roots. Generally, soil insects require longer exposure time to be infected and killed by insect pathogens, for example, soil-applied M. anisopliae conidiated on millet grains at the rate of 10 7 conidia g −1 soil resulted in the death of 50% of the population of the subterranean scarab larvae ( Adoryphorus couloni ) after 19 days in laboratory conditions [ 66 ]. Similarly, wireworms ( Agriotes sp.)…”
Section: Discussionmentioning
confidence: 99%